Direct determination of one‐dimensional interphase structures using normalized crystal truncation rod analysis. Issue 3 (20th April 2018) - Kawaguchi, Tomoya; Liu, Yihua; Reiter, Anthony; Cammarota, Christian; Pierce, Michael S.; You, Hoydoo
Abstract : Direct inversion of normalized crystal truncation rods to reconstruct real‐space interface structures was performed by retrieving the phase information using Hilbert transformation (Kramers–Kronig relation). Abstract : A one‐dimensional non‐iterative direct method was employed for normalized crystal truncation rod analysis. The non‐iterative approach, utilizing the Kramers–Kronig relation, avoids the ambiguities due to an improper initial model or incomplete convergence in the conventional iterative methods. The validity and limitations of the present method are demonstrated through both numerical simulations and experiments with Pt(111) in a 0.1 M CsF aqueous solution. The present method is compared with conventional iterative phase‐retrieval methods.